On the Improvement of Instruction in Higher Education A Bibliography - McKnight, Philip C., Comp.; Paskal, Mark A., Comp.; Kansas Univ., Lawrence ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1973)
This bibliography was compiled with the purpose of acquainting those interested in the improvement of teaching in higher education with various relevant sources. The bibliography is divided into four sections. The first section is concerned with sources relevant to instruction at all levels and thus lists publications dealing with theory and research, particularly in psychology and sociology. The second section is oriented to higher education and includes sources on faculty, students, and on the future of higher education. The third section deals with instruction per se in higher education and included sources related to classroom instruction, student evaluation of teaching, and the use of media and innovative curricula. The final section of the bibliography offers a representative selection of other sources related to teaching. (Author/HS)
Sponsoring Agency: Danforth Foundation, St. Louis, MO.
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Bibliographies; College Faculty; Educational Improvement; Educational Quality; Higher Education; Professors; Teacher Effectiveness; Teacher Improvement